Thermal Sensor Circuit Using Thermography for Temperature-Controlled Laser Hyperthermia. (9th October 2017) - Nomura, Shinsuke; Arake, Masashi; Morimoto, Yuji; Tsujimoto, Hironori; Miyazaki, Hiromi; Saitoh, Daizoh; Shinomiya, Nariyoshi; Hase, Kazuo; Yamamoto, Junji; Ueno, Hideki
Abstract : Laser hyperthermia is a powerful therapeutic modality that suppresses the growth of proliferative lesions. In hyperthermia, the optimal temperature range is dependent on the disease; thus, a temperature-driven laser output control system is desirable. Such a laser output control system, integrated with a thermal sensor circuit based on thermography, has been established. In this study, the feasibility of the developed system was examined by irradiating mouse skin. The system is composed of a thermograph, a thermal sensor circuit (PC and microcontroller), and an infrared laser. Based on the maximum temperature in the laser-irradiated area acquired every 100 ms during irradiation, the laser power was controlled such that the maximum temperature was maintained at a preset value. Temperature-controlled laser hyperthermia using the thermal sensor circuit was shown to suppress temperature fluctuations during irradiation (SD 0.14°C) to less than 1/10 of those seen without the thermal sensor circuit (SD 1.6°C). The thermal sensor circuit was able to satisfactorily stabilize the temperature at the preset value. This system can therefore provide noncontact laser hyperthermia with the ability to maintain a constant temperature in the irradiated area.